Proceedings of the 4th International Symposium on Health Research (ISHR 2019) 2020
DOI: 10.2991/ahsr.k.200215.005
|View full text |Cite
|
Sign up to set email alerts
|

Potential Association of Sanitation Factors on Stunting Incidences Among Children Under Age 5 in Bali Province, Indonesia

Abstract: Some sub-districts in Bali province have stunting prevalence more that national average which might be associated with the environmental health condition in those areas. This study aimed to examine the association between environmental health factors with stunting prevalence among children age 2-5 years. Case-control study was conducted at Karangasem district with 101 case and 101 control. Cases were obtained from the list of stunted children from the result of PSG 2017 in 4 sub-districts. The controls were ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
1
0
2
Order By: Relevance
“…Improper handling of the baduta poop is a risk factor for stunting (OR=3.03), and respondents who handle the baduta poop in a bad manner can cause children to be at risk 3.0 times greater for stunting. This research is in line with the findings of Dwipayanti et al, (2020) in the Province of Bali, which found that individuals who do not dispose of infant faeces in latrines are a risk factor for stunting in children (OR=2.90).…”
Section: Handling Of Toddler Faecessupporting
confidence: 91%
“…Improper handling of the baduta poop is a risk factor for stunting (OR=3.03), and respondents who handle the baduta poop in a bad manner can cause children to be at risk 3.0 times greater for stunting. This research is in line with the findings of Dwipayanti et al, (2020) in the Province of Bali, which found that individuals who do not dispose of infant faeces in latrines are a risk factor for stunting in children (OR=2.90).…”
Section: Handling Of Toddler Faecessupporting
confidence: 91%
“…A survey from 13 provinces of Indonesia found that households with good sanitation contributed positively to reducing the incidence of stunting intoddlers from 2007 to 2014. Most of the findings in rural areas of Indonesia related to sanitation using toilet facilities ranging from ownership, types, the use of septic tanks, hygiene, open defecation behavior and improper disposal of toddler feces were associated with an increase in stunting in toddlers in Indonesia [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] .…”
Section: Discussionmentioning
confidence: 99%
“…Sebagian besar hasil temuan di wilayah Pedesaan Indonesia terkait sanitasi penggunaan fasilitas jamban mulai dari kepemilikan jamban, jenis jamban, jamban tidak menggunakan septik tangki , kebersihan jamban, perilaku Open defecation dan pembuangan tinja balita tidak pada jamban berhubungan dengan peningkatan stunting pada balita di Indonesia (Ahmadi et al, 2020;Badriyah & Syafiq, 2017;Choirunnisa et al, 2020;Dwipayanti et al, 2020;Fikru & Doorslaer, 2019;Hasanah & Susanti., 2018;;Hafid., et al, 2017;Hasan & Kadarusman., 2018;Herawati et al, 2020;Nasrul, 2018;Otsuka et al, 2019;Rahayu et al, 2017;Lobo et al, 2020;Siswati, 2018;Torlesse. et al, 2016;Wiyono et al, 2019;cahyono et al, 2016;Rahayu dan Darmawan, 2019;Zairinayati & Purnama, 2019) .…”
Section: Faktor Sanitasi Dengan Kejadian Stunting Pada Balita DI Indounclassified